Administrators’ Conflict Management and Strategies - T. Kilag, Osias Kit; M. Largo, Joan; R. Rabillas, Annabelle; E. Kilag, Fernando; A. Angtud, Mark Kevin; P. Book, John Francis; Sasan, John Michael (Journal of Higher Education and Academic Advancement, 2024)
This study seeks to identify key elements to workplace conflict. A descriptive phenomenological design, a qualitative method used by the researchers to gain a deeper knowledge of the phenomenon, was used. The experiences of the informants led to the development of five themes. The themes supported the necessity of conflict management, emphasizing its significance particularly in the relationship between administrators and those they supervise. Additionally, their individual families might find it significant. Lessons on how to prevent disputes in every circumstance or job may be learned from the many themes. Hurtful comments, misunderstandings, failing to handle obligations, and failing to delegate jobs were the causes of the conflicts. But these disputes were successfully resolved owing to effective communication and the mediation of friends and coworkers. Conflict can be supported and influenced by effective conflict management. The third theme is "Well-managed conflicts are opportunities for cooperation." The fourth theme is that handling conflict helps people develop as people. Theme No. 5: Conflict situations should be handled completely.